1996
DOI: 10.1111/j.1445-2197.1996.tb01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Pulmonary Metastases From Nasopharyngeal Carcinoma

Abstract: Background: Nasopharyngeal carcinoma (NPC), unlike other head and neck cancers, is known for its propensity for distant metastases. Chemotherapy remains the mainstay of treatment because of this and the chemosensitivity of the tumour, but long‐term control is rare. The surgical management of pulmonary metastases of other extrathoracic malignancies prompted this review of surgical management of patients with NPC. Methods: Thirteen thoracotomies were performed in 12 patients with pulmonary metastases as the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, the survival of NPC patients with metachronous metastasis after primary radiotherapy was shown to increase following local treatment of solitary liver or pulmonary metastatic lesions[28][31]. Notably, it was reported that a NPC patient with a synchronous solitary bone metastasis gained more than 5 years of disease-free survival after a combination of systemic chemotherapy, locoregional radiotherapy, and radiotherapy for metastatic bone disease[32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival of NPC patients with metachronous metastasis after primary radiotherapy was shown to increase following local treatment of solitary liver or pulmonary metastatic lesions[28][31]. Notably, it was reported that a NPC patient with a synchronous solitary bone metastasis gained more than 5 years of disease-free survival after a combination of systemic chemotherapy, locoregional radiotherapy, and radiotherapy for metastatic bone disease[32].…”
Section: Discussionmentioning
confidence: 99%
“…Our results concurred closely with another study of lung metastasis of NPC in Hong Kong that NPC patients with lung metastasis(es) alone ( n = 41) appeared to have a distinctively better prognosis, with a hazards ratio (HR) of 0.41 compared with other types of metastasis(es) [7]. In other studies, intrathoracic metastasis(es) (lung and/or mediastinal nodes) was considered as a good prognostic factor in metastatic NPC [8,20,21]. However, to our knowledge, no literature has identified the precise predictive factors for the prognosis in this specific group.…”
Section: Discussionmentioning
confidence: 99%
“…Although several publications have shown in small cohorts that NPC patients with lung metastasis(es) alone may benefit from combined therapy, no data exists in larger patient cohorts [8,20-22]. We set out this retrospective study thought to add more evidences to help define the predictive factors of this group in a large cohort, and to facilitate the selection of the appropriate group to receive combined modality treatment for a better survival.…”
Section: Introductionmentioning
confidence: 99%
“…First, mediastinal and hilar lymphadenopathy constitute a significant component of intrathoracic metastases, which developed after localregional treatment of NPC. 13 Moreover, patients with intrathoracic metastases, including mediastinal nodal metastases, are known to have a prognosis distinctly better than other distant metastatic sites, 8,18,19 and some of the patients with mediastinal nodal metastases had prolonged survival after mediastinal radiation therapy. 18 Second, the orderly spread of nodal metastases in the cephalad-caudal direction in NPC 5 suggests the possibility that the superior mediastinal and axillary nodes could be the next echelon for lymphatic spread after supraclavicular nodal metastases.…”
Section: Discussionmentioning
confidence: 99%